Self-Concept on Learning English Reading Comprehension of Sophomore Secondary School Students - Syamsul Una; Rizal Arisman; Siti Irsawati; Rista Rista (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study aims to observe the senior high school learners’ self-concept in learning English reading comprehension. A survey method was applied in this study by utilizing a Self-Concept Inventory (SCI) to obtain the data on self-knowledge, self-expectation, and self-evaluation. There were 87 students, consisting of 42 male and 47 female students, involved as the research sample. The results of this study showed that the mean score of the students’ self-knowledge was 2.94, indicating that the students generally possess a high level of self-knowledge, especially in emotional awareness, acceptance of criticism, and social responsibility. The mean score of self-expectation was 2.98, affirming that participants have a strong positive self-expectation. The mean score of self-evaluation was 3.11, implying that the students perceive themselves positively across all these self-evaluation dimensions. Meanwhile, for overall self-concept, the mean score achieved 3.00 expressed that the students possessed a high level of self-concept (ranging 2.9 – 3.5), in which this self-concept is usually applied in learning reading comprehension. With higher academic self-concept, students tend to put more effort into understanding reading texts, are more motivated, and generally perform better in reading tasks compared to those with lower self-concept.